Nexus between renewable energy efficiency, financial literacy, and green microfinance: The case of women microfinance group - Min-Sun Kim; Andrian Dolfriandra Huruta; Cheng-Wen Lee (Economic Review: Journal of Economics and Business, 2024)
This study aims to investigate the role of financial literacy in green microfinance investment in women's microfinance groups. It considers renewable energy efficiency and financial literacy as factors that influence green microfinance. The study's main goal is to examine the direct and indirect relationships among these three factors. The findings suggest that a pro-climate (SDG 13) policy in response to energy efficiency (SDG 7) is supported by pro-local knowledge-based financial inclusion (SDG 4). Energy efficiency, climate action, and local knowledge-based financial inclusion are seen as policy options to reduce poverty in rural areas in East Sumba.
Keywords: C12; L26; 330; financial literacy; green microfinance; PLS-SEM; renewable energy efficiency; women microfinance group